Cannabinoid receptor type 2 is upregulated in synovium following joint injury and mediates anti-inflammatory effects in synovial fibroblasts and macrophages. Issue 12 (December 2021) - Rzeczycki, P.; Rasner, C.; Lammlin, L.; Junginger, L.; Goldman, S.; Bergman, R.; Redding, S.; Knights, A.J.; Elliott, M.; Maerz, T.
Summary: Objective: Joint injury-induced perturbations to the endocannabinoid system (ECS), a regulator of both inflammation and nociception, remain largely uncharacterized. We employed a mouse model of ACL rupture to assess alterations to nociception, inflammation, and the ECS while using in vitro models to determine whether CB2 agonism can mitigate inflammatory signaling in macrophages and fibroblast-like synoviocytes (FLS). Design: Mice underwent noninvasive ACL rupture (ACLR) via tibial compression-based loading. Nociception was measured longitudinally using mechanical allodynia and knee hyperalgesia testing. Synovitis was assessed using histological scoring and histomorphometry. Gene and protein markers of inflammation were characterized in whole joints and synovium. Immunohistochemistry assessed injury-induced alterations to CB1+, CB2+, and F4/80+ cells in synovium. To assess whether CB2 agonism can inhibit pro-inflammatory macrophage polarization, murine bone marrow-derived macrophages (mBMDM) were stimulated with IL-1β or conditioned medium from IL-1β-treated FLS and treated with vehicle (DMSO), the CB2 agonist HU308, or cannabidiol (CBD). Macrophage polarization was assessed as the ratio of M1-associated ( IL1b, MMP1b, and IL6 ) to M2-associated ( IL10, IL4, and CD206) gene expression. Human FLS (hFLS) isolated from synovial tissue of OA patients were treated with vehicle (DMSO) or HU308 following TNF-α or IL-1β stimulation to assess inhibition of catabolic/inflammatory gene expression. Results: ACLR induces synovitis, progressively-worsening PTOA severity, and an immediate and sustained increase in both mechanical allodynia and knee hyperalgesia, which persist beyond the resolution of molecular inflammation. Enrichment of CB2, but not CB1, was observed in ACLR synovium at 3d, 14d, and 28d, and CB2 was found to be associated with F4/80 (+) cells, which are increased in number in ACLR synovium at all time points. The CB2 agonist HU308 strongly inhibited mBMDM M1-type polarization following stimulation with either IL-1β or conditioned medium from IL-1β-treated mFLS, which was characterized by reductions in Il1b, Mmp1b, and Il6 and increases in Cd206 gene expression. Cannabidiol similarly inhibited IL-1β-induced mBMDM M1 polarization via a reduction in Il1b and an increase in Cd206 and Il4 gene expression. Lastly, in OA hFLS, HU308 treatment inhibited IL-1β-induced CCL2, MMP1, MMP3, and IL6 expression and further inhibited TNF-α-induced CCL2, MMP1, and GMCSF expression, demonstrating human OA-relevant anti-inflammatory effects by targeting CB2. Conclusions: Joint injury perturbs the intra-articular ECS, characterized by an increase in synovial F4/80(+) cells, which express CB2, but not CB1. Targeting CB2 in murine macrophages and human FLS induced potent anti-inflammatory and anti-catabolic effects, which indicates that the CB2 receptor plays a key role in regulating inflammatory signaling in the two primary effector cells in the synovium. The intraarticular ECS is therefore a potential therapeutic target for blocking pathological inflammation in future disease-modifying PTOA treatments.